Niqab and Stereotypes: Analyzing the Social Perceptions and Symbolic Meaning at UIN Sunan Ampel Surabaya - Mohamad Refansa Rafly Pasa; Haqqul Yaqin (Faculty of Ushuluddin and Philosophy, 2024)
The phenomenon of stereotypes against women who wear the niqab is still prevalent among students, particularly at UIN Sunan Ampel Surabaya (UINSA). The niqab, which is generally associated with a religious symbol, is often misunderstood and linked to negative images, especially those related to radical groups and terrorism. This study aims to reveal how stereotypes toward women wearing the niqab are formed among UINSA students and to analyze the differences in the actual meaning of the niqab symbol. Using symbolic interactionism theory, this study examines the differences between the campus community’s perceptions of the niqab and the personal reasons held by women who wear it. The research method used is descriptive qualitative with in-depth interviews and observations of students who are the research subjects and women who wear the niqab as the research subjects. The study results indicate that the stereotypes developed among UINSA students are more influenced by a lack of understanding of the meaning behind wearing the niqab, which often differs from the general perceptions that have developed in the campus community. This study is expected to contribute to correcting misunderstandings and strengthening a more inclusive understanding of religious symbols in the social context of Indonesia.